FROM SUBORDINATION TO ACCUMULATION: THE POST-REFORM TRAJECTORY OF POLRI'S ECONOMIC-POLITICAL CAPITAL IN INDONESIA - Gabriela Adeline Thurana; Riaty Raffiudin (RADJA PUBLIKA, 2026)
The 1998 Reform and the separation of the Indonesian National Police (Kepolisian Negara Republik Indonesia, Polri) from the Armed Forces of the Republic of Indonesia (Tentara Nasional Indonesia/Angkatan Bersenjata Republik Indonesia, TNI/ABRI) are widely understood as a milestone in Indonesia's democratic transition in the security sector. However, this article argues that this institutional separation constituted a critical juncture that paradoxically expanded rather than curtailed Polri's economic-political capital accumulation. Drawing on Chambers & Waitoolkiat's (2017) khaki capital framework and historical institutionalism, the article demonstrates that the institutional autonomy Polri gained was not matched by commensurate accountability mechanisms—transforming the institution from one that was structurally constrained under ABRI's military dominance into one that enjoyed far greater capacity to accumulate economic-political capital independently. This transformation operated through three mutually reinforcing mechanisms: institutional separation placing Polri directly under the President; intense TNI-Polri competition over khaki capital domains that evolved into a rent-sharing ecosystem; and regulatory asymmetry that left Polri without effective business prohibitions, while simultaneously leaving both internal and external oversight mechanisms—including the Inspectorate General (Inspektorat Pengawasan Umum, Itwasum) Polri and the National Police Commission (Komisi Kepolisian Nasional, Kompolnas) too weak to constrain informal economic accumulation.